147k views
2 votes
-3x-3y=3
y=-5x-17
Substitution
Plz help if you can I would appreciate it

User Cyberfly
by
5.9k points

1 Answer

2 votes
First substitute the second equation into the first one:
-3x - 3(-5x - 17) = 3
Next distribute the parenthesis:
-3x + 15x + 51 = 3
Then combine like terms:
12x + 51 = 3
Now subtract 51 from each side:
12x = 48
Lastly to get x, divide each side by 12:
x = 4
Now put this into the second equation:
y = -5(4) - 17
Multiply:
y = -20 - 17
And subtract:
y = -37
The solution is (4,-37). Hope this helps!
User ULLAS K
by
6.0k points